Immunoprotective Efficacy of Six In vivo-Induced Antigens against Actinobacillus pleuropneumoniae as Potential Vaccine Candidates in Murine Model - Zhang, Fei; Cao, Sanjie; Zhu, Zhuang; Yang, Yusheng; Wen, Xintian; Chang, Yung-Fu; Huang, Xiaobo; Wu, Rui; Wen, Yiping; Yan, Qigui; Huang, Yong; Ma, Xiaoping; et al. (Frontiers in Microbiology, 2016)
Six in vivo-induced (IVI) antigens-RnhB, GalU, GalT, Apl_1061, Apl_1166, and HflX were selected for a vaccine trial in a mouse model. The results showed that the IgG levels in each immune group was significantly higher than that of the negative control (P<0.001). Except rRnhB group, proliferation of splenocytes was observed in all immunized groups and a relatively higher proliferation activity was observed in rGalU and rGalT groups (P<0.05). In the rGalT vaccinated group, the proportion of CD4+ T cells in spleen was significant higher than that of negative control (P<0.05). Moreover, proportions of CD4+ T cells in other vaccinated groups were all up-regulated to varying degrees. Up-regulation of both Th1 (IFN-γ, IL-2) and Th2 (IL-4) cytokines were detected. A survival rate of 87.5%, 62.5% and 62.5% were obtained among rGalT, rAPL_1166 and rHflX group, respectively while the remaining three groups was only 25%. Histopathological analyses of lungs indicated that surviving animals from the vaccinated groups showed relatively normal pulmonary structure alveoli. These findings confirm that IVI antigens used as vaccine candidates provide partial protection against APP infection in a mouse model, which could be used as potential vaccine candidates in piglets.